Vegetable proteins as functional food - Nowicka, Grażyna (Studia Ecologiae et Bioethicae, 2006)
The primary role of the diet is to provide adequate quantities of nutrients to meet metabolic requirements and maintain optimal health. However, it has been shown that certain types of food or specific food components can affect a variety of body functions and provide specific health benefits. Diet containing such types of food may promote better health and play an important role in disease prevention by reducing the risk of certain chronic diseases. Vegetable proteins, especially legume proteins, have been recognized as factors influencing lipid metabolism. Hypocholesterolemic effects of different legume proteins have been documented. Hypotensive action of bioactive peptides derived from soy and lupin proteins has been reported. In soy a peptide of anti-mitotic activity was found and it may play a significant role in suppression of tumor development and cancer prevention. Diet rich in vegetables and vegetable proteins is related to lower risk of cardiovascular and cancer mortality.